2011
DOI: 10.1093/eurpub/ckr080
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and health-related quality of life in adults: a population based study in five cities of China

Abstract: Obesity impaired physical but not mental health, and the impairments varied between genders. Public health agencies and government should emphasize the impairments of obesity on physical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 27 publications
7
46
2
3
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18] Most reports consistently show the following: (1) there is a J-or U-shaped relationship linking physical HRQoL and BMI, with higher risk for poorer HRQoL in the underweight and overweight/ with obesity subjects; (2) findings for psychosocial impairment are inconclusive and detect little or no effect; [7][8][9][10][11]13,19,20 (3) physical, and to a lesser extent psychosocial, impairment is more severe in women than men. 7,8,11,12,[21][22][23] There are few data available to explain the different consequences of obesity between the sexes because most analyses exploring the relationship between BMI and HRQoL account for sex as a confounder to adjust for and do not report stratified results. Among the various explanations that have been proposed, a higher discomfort caused by overweight has been observed in women, 24 and women have been found to develop body image dissatisfaction at higher rates compared with men.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18] Most reports consistently show the following: (1) there is a J-or U-shaped relationship linking physical HRQoL and BMI, with higher risk for poorer HRQoL in the underweight and overweight/ with obesity subjects; (2) findings for psychosocial impairment are inconclusive and detect little or no effect; [7][8][9][10][11]13,19,20 (3) physical, and to a lesser extent psychosocial, impairment is more severe in women than men. 7,8,11,12,[21][22][23] There are few data available to explain the different consequences of obesity between the sexes because most analyses exploring the relationship between BMI and HRQoL account for sex as a confounder to adjust for and do not report stratified results. Among the various explanations that have been proposed, a higher discomfort caused by overweight has been observed in women, 24 and women have been found to develop body image dissatisfaction at higher rates compared with men.…”
mentioning
confidence: 99%
“…These factors affect the mobility of the individual. [27][28][29] Due to this, the mobility is better in the individuals in the rural areas than in the urban areas and thus the risk of falls is lower in the individuals in rural areas. In our study, it was observed that the average mobility scores which was measured with TUG test showed lower time scores in rural postmenopausal women as compared to urban postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…U urbanoj populaciji Beograda, istraživači su primenom upitnika SF-36 našli da prekomerna težina korelira sa poremećajem fizičkog, ali ne i mentalnog HRQoL nezavisno od pola [Vasiljevic 2008]. Do sličnog rezultata se došlo u opštoj kineskoj populaciji gojaznih žena i žena normalne telesne težine, gde je HRQoL, meren upitnikom SF-36, značajno oštećen gojaznošću u četiri skale fizičkog zdravlja i samo u jednoj od četiri skale mentalnog zdravlja -skala vitalnosti, pa je zaključeno da gojaznost pogađa samo fizičko, a ne i mentalno zdravlje [Wang 2012]. I većina drugih istraživanja pokazuje da negativni efekti preterane telesne težine više pogađaju fizičke nego mentalne komponente HRQoL u opštoj populaciji.…”
Section: Diskusija Studije Determinanti Zdravstvenogunclassified
“…Uz pretrudničku gojaznost, ekscesivno gestaciono dobijanje težine je jedan od indikatora neželjenih ishoda trudnoće. Iako gojaznost može biti rizik za nastanak obstetričkih komplikacija, podaci o trendovima gojaznosti u trudnoći su oskudni [Wang 2012]. U nekoliko studija praćena je telesna težina trudnica Kako gojaznost tako i anoreksija predstavljaju multifaktorijalne bolesti, povezane sa fizičkim i emocionalnim problemima.…”
Section: Diskusija Studije Determinanti Zdravstvenogunclassified
See 1 more Smart Citation